2021
DOI: 10.15562/ijn.v4i1.142
|View full text |Cite
|
Sign up to set email alerts
|

The Indonesian Central Nervous System Tumors Registry (Ina-CTR) : 7 years result from single institution of primary brain tumor epidemiology

Abstract: Background: Primary brain tumor is one of the most cases the neurosurgeon could found, despite good neurosurgery progress, still there is no epidemiologic data that collected from Indonesia as a low middle-income country in Asia.Objective: The Indonesian central nervous system tumors registry (Ina-CTR) aims to provide epidemiologic data on primary brain tumor in Indonesia and to provoke more wider data collection in Indonesia as a whole nation. Methods: We collect data from medical records retrospectively from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…[23] Wahyuhadi et al reported a register of 1540 patients who underwent surgery for brain tumors during 2012-2018 in a single general academic hospital in Surabaya, East Java. [31] Tandian et al made a specific report on the characteristics, management, and outcome of 44 medulloblastoma patients surgically managed from 2011 to 2018 in one national referral hospital in Jakarta. [29] Rosyidi et al registered the characteristics and clinical outcomes of 209 TBI patients managed from 2015 to 2017 in West Nusa Tenggara.…”
Section: Other Indonesian Neurosurgery Registriesmentioning
confidence: 99%
“…[23] Wahyuhadi et al reported a register of 1540 patients who underwent surgery for brain tumors during 2012-2018 in a single general academic hospital in Surabaya, East Java. [31] Tandian et al made a specific report on the characteristics, management, and outcome of 44 medulloblastoma patients surgically managed from 2011 to 2018 in one national referral hospital in Jakarta. [29] Rosyidi et al registered the characteristics and clinical outcomes of 209 TBI patients managed from 2015 to 2017 in West Nusa Tenggara.…”
Section: Other Indonesian Neurosurgery Registriesmentioning
confidence: 99%
“…Moreover, the cysts are sporadic or evolve congenitally in the central nervous system and represent less than 0.4% of all cyst-like lesions. Those indications are commonly found in East Java [1] , [2] , [3] . The cavitations emerge mainly in intracranial locations, such as intraparenchymal, intraventricular, and subarachnoid spaces; the spinal cord is an unusual site of occurrence [1 , 4] .…”
Section: Introductionmentioning
confidence: 97%